Morphology of the Preimaginal Stages of Lasioptera donacis Coutin (Diptera: Cecidomyiidae), a Candidate Biocontrol Agent for Giant Arundo Cane - Donald B. Thomas; John A. Goolsby (Psyche: A Journal of Entomology)
The larval stages of Lasioptera donacis Coutin consist of three instars which develop within the mesophyll of the leaf sheaths of Arundo donax (L.) (Poaceae). The larvae feed aggregatively on mycelia of an ambrosia fungus. The third instars are similar to other members of the genus except for a three-pronged spatula (typically two-pronged) and five lateral papillae (typically four) and with a nonbristled first instar. A related species, L. arundinis (Schiner) which breeds on fungus in Phragmites (Poaceae), also has a three-pronged spatula and five lateral papillae but has a bristled first instar. The third instar of L. donacis has a feeding and a nonfeeding prepupal stage. Papillae associated with the spatula are sensory organs, sensilla chaetica, sensilla trichodea, and sensilla ampullacea, perhaps related to extraoral digestion of the fungal mycelia. Pupation occurs in the host plant within a silken cocoon. Egression of the adult is through an escape hatch excavated by the third instar.